The Role of Academic Self Efficacy, Social Supoort Teachers Against Self Regulated Learning Students who are Forced at the Inclusion School with Academic Self Concept as a Mediator Variable - Bibit Mulyana; Mareyke M.A.W. Tairas; Dewi Retno Suminar (Universitas Ahmad Dahlan, 2019)
Students with physical disabilities experience many problems with learning. The self-regulated learning model is an independent learning model that teaches students how to effectively organize and manage themselves, to ensure optimal learning outcomes. Our purpose is to analyze how teacher support and academic self-efficacy could influence the self-regulated learning model, specifically with academic self-efficacy as a mediating variable. We used survey as our research instrument. Meanwhile, the analysis method used path analysis. Our findings show that academic self-efficacy could significantly increase the self-regulated learning of physically disabled students. Teacher support had a minimal effect on improving the self-regulated learning of physically disabled students. We also found the importance of academic self-concept as a mediator in increasing self-regulated learning of physically disabled students. Future research is advised to include other social support variables such as parental and peer support into the model. Our findings can be used as a reference for developing a curriculum on a self-regulated learning model for disabled students.